Business information systems : 21st International Conference, BIS 2018, Berlin, Germany, July 18-20, 2018, proceedings /: 21st International Conference, BIS 2018, Berlin, Germany, July 18-20, 2018, proceedings. (2018) - Unknown
No abstract available